Czech.Math.J. 2019
DOI: 10.21136/cmj.2019.0389-18
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of partial isometries and two special kinds of EP elements

Abstract: Institute of Mathematics of the Czech Academy of Sciences provides access to digitized documents strictly for personal use. Each copy of any part of this document must contain these Terms of use.This document has been digitized, optimized for electronic delivery and stamped with digital signature within the project DML-CZ: The Czech Digital Mathematics Library http://dml.cz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…S. Z. Xu, J. L. Chen and J. Ben ítez in [14] showed that the EP elements in R can be characterized by three equations, which are (xa) * = xa, xa 2 = a and ax 2 = x. In addition, more interesting results on EP elements and partial isometries can also be found in [2,3,7,10,9,14,18].…”
Section: Yue Sui Yimin Huang and Junchao Weimentioning
confidence: 97%
“…S. Z. Xu, J. L. Chen and J. Ben ítez in [14] showed that the EP elements in R can be characterized by three equations, which are (xa) * = xa, xa 2 = a and ax 2 = x. In addition, more interesting results on EP elements and partial isometries can also be found in [2,3,7,10,9,14,18].…”
Section: Yue Sui Yimin Huang and Junchao Weimentioning
confidence: 97%
“…There are many studies on EP element, P I element and strongly EP element, see for example [2,4,5,6,7,8,9,10].…”
Section: Characterizations Of Partial Isometries In Rings With Involution 305mentioning
confidence: 99%
“…In addition, some characterizations of EP elements in ring with involution were given. Recently, some studies on partial isometries and EP elements have come to some meaningful conclusions in [5,8,10,11]. Moreover, the description of EP elements by using solutions of equations has been explored in [8,11,12].…”
Section: Introductionmentioning
confidence: 99%